Business Sustainability Analysis of Street Vendors: A Case Study in Salletto Village, Simboro District, Mamuju Regency - Khairul Haq; Yati Heryati; Muhammad Arsyad; Supriadi; Ratna (LP2M IAIN Palopo, 2026)
This study aims to analyze the sustainability conditions of street vendors and identify the supporting and inhibiting factors faced by street vendors in Salletto Village Market, Simboro District, Mamuju Regency. This study uses a qualitative approach with a case study design. Informants were selected through purposive sampling and consisted of one key informant (the Head of Salletto Village), 15 main informants (street vendors who had been operating for at least one year), and supporting informants from the communities of Pasada and Ganno hamlets. Data were collected through in-depth interviews, participant observation, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. Data validity was tested through source and method triangulation. The results show that the sustainability of street vendors in Salletto Village is more oriented toward meeting basic household needs (livelihood activities), with stable daily capital turnover, although there is not yet a strong orientation toward capital expansion. The main supporting factors include low operating costs, flexible payment systems (credit/installments), access to local microfinance, communal social ties, and the application of Islamic business ethics (sidiq and amanah). The inhibiting factors include low financial literacy and poor financial record-keeping, dependence on middlemen-based supply chains from Mamuju City, intense competition in basic commodities, and limited technological adaptation. This study recommends assistance in simple financial record-keeping and facilitation by the village government to break inefficient supply chains.